CPMD/GULP QM/MM interface for modeling periodic solids: Implementation and its application in the study of Y‐zeolite supported Rhn clusters. Issue 18 (19th April 2016) - Sahoo, Sudhir K.; Nair, Nisanth N.
Abstract : We report here the development of hybrid quantum mechanics/molecular mechanics (QM/MM) interface between the plane‐wave density functional theory based CPMD code and the empirical force‐field based GULP code for modeling periodic solids and surfaces. The hybrid QM/MM interface is based on the electrostatic coupling between QM and MM regions. The interface is designed for carrying out full relaxation of all the QM and MM atoms during geometry optimizations and molecular dynamics simulations, including the boundary atoms. Both Born–Oppenheimer and Car–Parrinello molecular dynamics schemes are enabled for the QM part during the QM/MM calculations. This interface has the advantage of parallelization of both the programs such that the QM and MM force evaluations can be carried out in parallel to model large systems. The interface program is first validated for total energy conservation and parallel scaling performance is benchmarked. Oxygen vacancy in α ‐cristobalite is then studied in detail and the results are compared with a fully QM calculation and experimental data. Subsequently, we use our implementation to investigate the structure of rhodium cluster (Rh n ; n  = 2 to 6) formed from Rh(C2 H4 )2 complex adsorbed within a cavity of Y‐zeolite in a reducible atmosphere of H2 gas. © 2016 Wiley Periodicals, Inc. Abstract : A highly parallel CPMD/GULP QM/MM Interface is developed here for performing molecular dynamics simulations of periodic solids. Application of this code for studying static and dynamic properties of zeolite supported Rh clusters is also presented.